1991
DOI: 10.1523/jneurosci.11-11-03297.1991
|View full text |Cite
|
Sign up to set email alerts
|

Segregation of callosal and association pathways during development in the visual cortex of the primate

Abstract: The segregation of callosal and association pathways in the developing visual cortex of the monkey was studied using the retrograde tracers fast blue and diamidino yellow. Quantitative analysis of the laminar distribution of labeled callosal and association neurons made it possible to reveal the shifting pattern of connections that characterizes the development of these two pathways. In the adult, callosal neurons are restricted to supragranular layers, where they are concentrated at the bottom of layer 3. Ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
35
0

Year Published

1996
1996
2004
2004

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 60 publications
5
35
0
Order By: Relevance
“…In contrast, two recent studies (Meisserel et al, 1991;Barone et al, 1995) have reported that the projection from V2 to V1 in the macaque initially involves a transient, excessive projection from the superficial layers. Their results were obtained using multiple large injections of fluorescent retrograde tracers into V1.…”
Section: Development In the Radial Dimensionmentioning
confidence: 79%
“…In contrast, two recent studies (Meisserel et al, 1991;Barone et al, 1995) have reported that the projection from V2 to V1 in the macaque initially involves a transient, excessive projection from the superficial layers. Their results were obtained using multiple large injections of fluorescent retrograde tracers into V1.…”
Section: Development In the Radial Dimensionmentioning
confidence: 79%
“…Interestingly, the neurons projecting from area VI to area MT, that are characterized by high levels of neurofilament protein, are all very large and have large axons, up to 3 /xm in diameter (Rockland, 1989(Rockland, , 1995, whereas short corticocortical connections are characterized by relatively lower levels of neurofilament protein immunoreactivity and originate from smaller neurons (Campbell et al, 1991;Hofetal., \995a,b, 1996). It should be kept in mind that the distribution of callosal connections in the primate visual system is not limited to the V1/V2 border, but that extensive sets of complex commissural projections exist in the prestriate cortex as well, that subserve additional roles such as completion of large receptive fields and interactions between field center and suppressive surrounds, and color constancy (Zeki, 1970;Van Essen et al, 1982;Antonini et al, 1983;Land et al, 1983;Maunsell & Van Essen, 1987;Spatz et al, 1987;Meissirel et al, 1991;Desimone et al, 1993). It should be kept in mind that the distribution of callosal connections in the primate visual system is not limited to the V1/V2 border, but that extensive sets of complex commissural projections exist in the prestriate cortex as well, that subserve additional roles such as completion of large receptive fields and interactions between field center and suppressive surrounds, and color constancy (Zeki, 1970;Van Essen et al, 1982;Antonini et al, 1983;Land et al, 1983;Maunsell & Van Essen, 1987;Spatz et al, 1987;Meissirel et al, 1991;Desimone et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Despite having a common topology and common morphologies and occupying similar laminar distributions in layers II/III and V, callosal and association projection neurons in the monkey neocortex have been reported to differ on the basis of terminal projections and are two separate populations of neurons that rarely have dual projections Goldman-Rakic, 1982, 1984;Andersen et al, 1985;Johnson et al, 1989;Meissirel et al, 1991). Similar studies performed in rats have previously shown that callosal projections in the developing cortex are initially widespread but that these callosal projections are later lost or "pruned" as ipsilateral projections are made to the motor cortex in areas corresponding to the barrel fields (Ivy et al, 1979(Ivy et al, , 1984Killackey, 1981, 1982;O'Leary et al, 1981).…”
mentioning
confidence: 99%